IL-6 and TNF-alpha production during active canine visceral leishmaniasis - de Lima, Valeria M. F.; Peiró, Juliana Regina [UNESP]; Vasconcelos, Rosemeri de Oliveira (Elsevier B.V., 2007)
We investigated the production of interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-alpha) during canine visceral leishmaniasis (VL) to gain a better understanding of the role of such multi-functional cytokines in parasite resistance. IL-6 and TNF-alpha levels were measured by capture ELISA in sera from 8 healthy dogs from a non-endemic area (control group) and in sera from 16 dogs from Aracatuba, SP, Brazil, an area endemic for leishmaniosis. The dogs from the endemic area were selected by positive ELISA serology against total Leishmania chagasi antigen, positive spleen imprints for Leishmania, and the presence of at least three clinical signs associated with active visceral leishmaniasis (fever, dermatitis, lymphoadenopathy, onychogryphosis, weight loss, cachexia, locomotory difficulty, conjunctivitis, epistaxis, hepatosplenomegaly, edema, and apathy).Enhanced systemic IL-6 production was found in sera from dogs with the active disease compared to healthy dogs (t-test, P < 0.05). In contrast, TNF-alpha did not differ between the two groups studied. There was no correlation between IL-6 production and anti-leishmanial antibody titers in the sera. Our findings suggest that IL-6 is a good marker of active disease during leishmaniasis, and that other cytokines may be involved in the hypergammaglobulinemia characteristic of canine visceral leishmaniasis. (c) 2006 Published by Elsevier B.V.
Keywords: Leishmania (leishmania) chagasi; visceral leishmaniasis; IL-6; TNF-alpha; cytokine